2019
DOI: 10.3389/fpsyg.2019.01040
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Follow-Up of a Randomized Controlled Trial Piloting a Mindfulness-Based Group Intervention for Adolescent Insulin Resistance

Abstract: Introduction To explore if a brief mindfulness-based intervention (MBI) leads to sustained, improved clinical outcomes in adolescents at-risk for type 2 diabetes (T2D). Methods Participants were 12–17y girls with overweight/obesity, elevated depression symptoms, and T2D family history participating in a randomized, controlled pilot trial of a six-session MBI vs. cognitive-behavioral therapy (CBT) group. At baseline and 1-year, mindfulness, depression, insulin resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 12 publications
(16 reference statements)
2
23
0
Order By: Relevance
“…For example, in Shomaker (2019) research, mindfulness training reduced insulin resistance in diabetic adolescents with oneyear follow-up (8).Also various meta-analysis showed that vitamin D can reduce insulin resistance in different physical conditions (23,24 About e cacy of vitamin D and mindfulness on IR above researches showed similarity of our data with previous research literature. mindfulness with develops basic physiological and/or behavioral factors that in uence IR such as physical activity, eating habits, sleep behaviors, and stress arousal, reduce insulin resistance.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…For example, in Shomaker (2019) research, mindfulness training reduced insulin resistance in diabetic adolescents with oneyear follow-up (8).Also various meta-analysis showed that vitamin D can reduce insulin resistance in different physical conditions (23,24 About e cacy of vitamin D and mindfulness on IR above researches showed similarity of our data with previous research literature. mindfulness with develops basic physiological and/or behavioral factors that in uence IR such as physical activity, eating habits, sleep behaviors, and stress arousal, reduce insulin resistance.…”
Section: Resultssupporting
confidence: 80%
“…Another treatment that demonstrated promising results in T2DM is mindfulness. based on previous researches, mindfulness can improves underlying physiological and behavioral determinants that in uence insulin resistance such as stress arousal, physical activity, sleep quality, and eating unhealthy habits (8). Also This treatment with improvement in immediate memory, thinking, and attention, can enhance cognitive function.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent randomized controlled trial by Shomaker et al explored the effect of brief MBIs and their relationship to sustained improved clinical outcomes in adolescents at risk for T2D …”
Section: Can Mindfulness Help Adolescents At Risk For T2d?mentioning
confidence: 99%
“…A recent randomized controlled trial by Shomaker et al explored the effect of brief MBIs and their relationship to sustained improved clinical outcomes in adolescents at risk for T2D. 7 This study is a single-center study that was conducted in adolescent girls between 12 and 17 years of age who were overweight or obese (BMI > 85%) with family history of T2D and depressive symptoms (total score ≥ 16 on the Center for Epidemiologic Studies Depression Scale).…”
Section: Can Mindfulness Help Adolescents At Risk For T2d?mentioning
confidence: 99%